Everyday [videorecording (DVD)] - Winterbottom, Michael; Simm, John; Henderson, Shirley, 1965- (distributed by MPI Home Video, 2014)
While Ian is in prison for drug smuggling, he will only see his wife and four children occasionally. Each member of his family will develop a different relationship with him as he is not there to offer the guidance of a father and husband. By the time he is allowed visits at home, their lives have become forever separated. However, the bonds that hold a family together will keep them forever linked.